On the feedback solution of a differential oligopoly game with capacity adjustment - Davide Dragone; Luca Lambertini; Arsen Palestini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
We propose a simple method for characterising analytically the feedback solution of oligopoly games with capital accumulation à la Solow-Swan. As a result, it becomes possible to contrast the feedback equilibrium against the corresponding one generated by open-loop information. Our method accommodates extensions of the stripped down oligopoly model in several directions. As an example, we expand the setup to include environmental effects and Pigouvian taxation.
Keywords: C73; L13; Q55; 330